PERBUATAN MENGAKU DIRINYA SEBAGAI ORANG LAIN DALAM PEMUNGUTAN SUARA PADA PEMILIHAN UMUM LEGISLATIF (STUDI KASUS: PUTUSAN NOMOR:01/PID.S/2014/P.N.MDN DAN PUTUSAN NOMOR:02/PID.B/2014/P.N.MDN) - Fifi Febiola Damanik; Syafruddin Kalo; Muhammad Ekaputra; Mirza Nasution (Universitas Sumatera Utara, 2018)
ABSTRACT Elections are the most important order in any democratic country as the most obvious form of state administration under the rule of law that must be done freely, honestly and fairly based on the sovereignty of the people. One of the most basic forms of elections is the granting of the right or the right choose which is part of Human Rights, which in its implementation rampant misuse of suffrage especially in Medan City. The issues raised in this thesis is how the regulation of the criminal act of legislative elections in Indonesia, how the role of election organizers in the effort to overcome the crime of elections in Medan City and how the application of criminal sanctions against the act of confessing himself as someone else in the voting on 2014 /PN.Mdn and verdict number: 02/Pid.B/2014/PN.Mdn. The research method used is the normative juridical research method descriptive analyst. This study uses the approach of legislation with data collection techniques namely library research supported by interviews to obtain more complete data. The results of the study indicate that the regulation on the criminal act of legislative elections in Indonesia has developed from the provisions that are only regulated in the Criminal Code up to Law Number. 8 of 2012 on General Election of House of Representatives, Regional Representative Council Regional People's Representative Assembly Provincial and Regency / City. The role of election organizers in the effort to overcome the criminal acts of legislative elections lies in integrated law enforcement center through penal facilities against law enforcement under the Bawaslu institution. The application of criminal sanctions against the acts of self-confessed based on two judgments of Medan District Court is considered not in accordance with the value of justice and does not realize the purpose of punishment based on the analysis of judges' ruling. Keywords : Acknowledging Himself as Others, General Election Legislative